Revolution and Politics in Russia Essays in Memory of B. I. Nicolaevsky - Kristof, Landis K. D.; Rainbowitch, Janet; Rabinowitch, Alexander (Indiana University Press, 1972)
Revolution and Politics in Russia: Essays in Memory of B. I. Nicolaevsky is a collection of distinguished articles on aspects of Russian political and intellectual history, of the nineteenth and twentieth centuries, written by internationally known authorities.